School Inclusion: Considerations About the Education Process of Teachers Who Teach Mathematics - Baraldi, Ivete Maria [UNESP]; Rosa, Fernanda Malinosky Coelho da; Capellini, Vera Lúcia Messias Fialho [UNESP]; Rosa, Erica Aparecida Capasio [UNESP]; Miranda, Edinéia Terezinha de Jesus [UNESP] (Springer Nature, 2019)
This chapter presents some considerations about the education process of teachers who teach mathematics in an inclusive context through narratives produced in three research studies, among others. In order to do so, we have chosen to discuss the challenges of these teachers in their daily life with students with disabilities, pointing out the necessary changes regarding both the education and the teaching and learning processes. We also discuss the fact that mathematics and special education teachers have difficulties in working in a collaborative way. Considering these issues, it is possible to state that the beliefs and conceptions about disabilities need to be deconstructed; schools need to be rethought as does the education process of teachers who teach mathematics. Additionally, we emphasize that collaborative teamwork is of fundamental importance for the construction of the inclusive school desired by society.
Keywords: Beliefs and conceptions of teachers; Education process of teachers of mathematics; Inclusive mathematical education; Special education teachers; Students with disability